ANALISIS PENGARUH MOTIVASI, STRESS, DAN REKAN KERJA TERHADAP KINERJA AUDITOR DI KANTOR BADAN PENGAWAS KEUANGAN DAN PEMBANGUNAN RIAU DAN SUMATERA UTARA - Yockie Permana; Rita Anugerah; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research purpose to analyzing the effect of motivation, stress and partner on the auditors performance at the Supervisor Agency of Finance and Development of Riau and North Sumatera Office of Riau and North Sumatera. The sampling method used purposive sampling as many as 47 functional auditors is in Riau office and 63 functional aditors in North Sumatera office. The data used is primary data collection method of data is using questionnaires. Data analysis method used in this study is multiple regression. Based on analysis result in this reseach, indicate that the independent variable motivation (X1), stress (X2) and partners (X3) is able to explain the effect on the dependent variable in the office of auditor performance Financial and Development Supervisory Agency of Riau and North Sumatera.Keywods: analysis, motivation, stress, partner, and auditor performance.